2019
DOI: 10.3389/fneur.2019.00542
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in Patients Seeking Care at an Orofacial Pain Unit

Abstract: Introduction: Orofacial pain and dysfunction include a broad range of disturbances among which pain and insomnia are some of the most common complaints. Sleep strengthens physiological and psychological resilience and is an absolute requirement for health. Insomnia is a common symptom or sleep disorder, yet data on its prevalence is sparse. Here we extracted data from the insomnia severity index which was part of the web-based interdisciplinary symptom evaluation (WISE) tool given to a large sample of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…Pain catastrophizing was demonstrated to mediate the effects of distress in OFP patients, which was attributed to the helplessness component of the PCS ( 50 ). Due to the sample overlap, the prevalence of moderate and severe grades of insomnia (15%) confirms the 16% we previously reported ( 13 ). A novel finding of this study is that approximately one in seven patients (14%) perceived injustice of a clinically relevant level.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Pain catastrophizing was demonstrated to mediate the effects of distress in OFP patients, which was attributed to the helplessness component of the PCS ( 50 ). Due to the sample overlap, the prevalence of moderate and severe grades of insomnia (15%) confirms the 16% we previously reported ( 13 ). A novel finding of this study is that approximately one in seven patients (14%) perceived injustice of a clinically relevant level.…”
Section: Discussionsupporting
confidence: 89%
“…On three additional scales from "not at all" (=0), "a little" (=1), "somewhat" (=2), "much" (=3), to "very much" (=4), the patient is asked how much he/she considers his/her sleep problem to interfere with daily activities, how noticeable the interference by his/her sleep problem is to others, and how worried/distressed the patient is because of his/her sleep problem. The maximum score is 28, with scales of "none" (0-7), "subthreshold" (8)(9)(10)(11)(12)(13)(14), "moderate" (15-21), or "severe" (>21). The following coefficient alpha has been reported: 0.74; test-retest reliability was not reported.…”
Section: Insomnia Severity Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…A high proportion of the study population reported clinically relevant insomnia (36%). This compares to 5.8% of general practice patients, 15.8% of care seekers at an orofacial pain unit, and 26.5% of chronic pain sufferers 31,32 . The high prevalence of sleep disorders in the present study is astonishing, as the average pain intensity was low.…”
Section: Discussionmentioning
confidence: 83%